PESANTREN DALAM BINGKAI SEJARAH PERJUANGAN KEMERDEKAAN INDONESIA - Royani, Ahmad (JURNAL ISLAM NUSANTARA, 2018)
Pesantren in the era of the struggle for independence not only serves as a scientific institution in the field of religion, but also serves as an institution to foster awareness and love of the homeland, awareness of nation and state. The issuance of Presidential Decree of the Republic of Indonesia as 22 Year 2015 on National Sanctuary, has confirmed and devoted the physical struggle of kyai and santri in defending, fighting and defending the Republic of Indonesia from invaders. This paper wants to know the history of the struggle of the pesantren when dealing with the invaders. Islamic figures with jihad to defend and defend Islam as has been done by kyai and pesantren